Innovative Curriculum Adaptation in Aligning Learning Content with 21st-Century Skills: A Case Study in Senior High Schools - Sulistyorini; Imam Fuadi; Muh Ibnu Sholeh; Sahri; Ahmed Hassan (CV. Gerasi Insan Nusantara, 2025)
The rapid advancement of technology and increasing global competition necessitate educational adaptation to 21st-century skills, including critical thinking, creativity, communication, and collaboration (4C). This study aims to analyze how innovative curriculum adaptation aligns learning content with these essential skills in several senior high schools (SMA) in Bojonegoro. Employing a qualitative case study approach, data were gathered through in-depth interviews with school principals and teachers, classroom observations, and document analysis. The findings reveal that schools have integrated digital technology into learning, implemented project-based learning (PBL), and conducted teacher training to enhance 21st-century skills. However, challenges such as inadequate technological facilities, varying levels of teacher readiness, and resistance to new teaching methodologies were identified. These findings suggest that innovative curriculum adaptation plays a significant role in preparing students for future challenges. Therefore, stronger support from schools, policymakers, and society is required to optimize the effectiveness of curriculum adaptation in fostering 21st-century competencies